Desain Dan Implementasi Aplikasi Penghafal Al-Quran Android Di Rumah Tahfidz Rabbunalloh Surabaya - Muhammad Ath Thariq Luqmana; Fidi Wincoko Putro; Mochammad Sholik (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
In general, some students also use a method called Tikrar, where the student repeats the verse. However, sometimes they're forgetting how many times it has been repeated. With Al-Quran Tikrar, there is a framework for memorizing Quran that can be found around the pages of the Quran. This helps to mark how many times the verse has been repeated using a ballpoint, pencil and such. But over time, the Quran would devreased its quality and condition, which causes the pages of the Quran seems dirty and damaged. The system works by making the memorizer or reciter be able to mark the number of times the verse has been repeated along with the level of fluency from